Answer:
96
Step-by-step explanation:
3*6=18*2=36
6*10=60*2=120
10*3=30*2=60
36+60+120=
216
Answer: 216 m
Step-by-step explanation:
2(10 x 6) = 120
2(6 x 3) = 36
2(10 x 3) = 60
120 + 36 + 60 = 216
Solution:
we are given that
Last year, sales at a book store increased from $5,000 to $10,000.
As we know that percentage increase is given by the formula
Percentage increase
Substitute the values we get
Percentage increase
Percentage increase %.
This year, sales decreased to $5,000 from $10,000.
Percentage Decrease
Substitute the values we get
Percentage Decrease
Percentage Decrease%.
Answer:
100%, 50%
Step-by-step explanation:
Answer:To solve the equation 4x + 17/18 - 13x - 2/17x - 32 + x/3 = 7x/12 - x + 16/36, we can follow these steps:
1. Combine like terms on each side of the equation.
On the left side, we have 4x - 13x + x/3. Simplifying this, we get -8x + x/3.
On the right side, we have 7x/12 - x + 16/36. Simplifying this, we get -5x/12 - x + 4/9.
2. Get rid of any fractions by multiplying each term by the least common denominator (LCD).
The LCD of 3, 12, and 36 is 36. Multiply each term on both sides of the equation by 36 to eliminate the fractions.
3. Simplify and combine like terms.
On the left side, we have -8x + x/3, which becomes -24x + x^2/3 after multiplying by 36.
On the right side, we have -5x/12 - x + 4/9, which becomes -15x - 3x + 16 after multiplying by 36.
4. Move all terms to one side of the equation.
Combining like terms, we get -24x + x^2/3 = -18x + 16.
5. Multiply the entire equation by 3 to eliminate the fraction.
This gives us -72x + x^2 = -54x + 48.
6. Move all terms to one side of the equation again.
Combining like terms, we get x^2 + 18x - 48 = 0.
At this point, the equation is a quadratic equation. To solve it, we can either factor or use the quadratic formula.